Analisis Swot dan Strategi Business Model Canvas Sebagai Strategi Pengembangan Usaha “Asik-Asik Fried Chicken”: SWOT Analysis and Business Model Canvas as a Franchise Business Development Strategy "Asik-Asik Fried Chicken" - Widiawati, Kristiana; Wibowo, Dwi Agung (Anterior Jurnal, 2024)
The growth and development of the fried chicken franchise business is increasing. Competition is also unavoidable. Business people need to develop and develop strategies so that the business can be sustainable. The research aims to find out the strategy used to develop the "Asik-Asik Friedchicken" fried chicken business using SWOT analysis and a business model canvas. Using qualitative methods through interviews and field observations with owners, employees and customers. The results of this research state that the fried chicken business "Asik-Asik Fried Chicken" can be developed using the SWOT matrix strategy. The strategy determined is strategy (SO) by establishing cooperation with new investors, strategy (ST) namely increasing product promotion, strategy (WO) namely adding a menu with various variants, both chili variants and processed chicken, strategy (WT) namely increasing quality services and changing packaging with packaging and equipped with attractive and trademarked brands. The results of the SWOT matrix can be carried out for business development through the business model canvas as strategy development (key factors), namely partners, activities, resources, product excellence, consumer relations, channels, market segmentation, costs/expenses, and income.